Differential vulnerability of interneurons in the epileptic hippocampus - Marx, Markus; Haas, Carola A.; Häussler, Ute (Frontiers in Cellular Neuroscience, 2013)
The loss of hippocampal interneurons has been considered one reason for the onset of temporal lobe epilepsy (TLE) by shifting the excitation-inhibition balance. Yet, there are many different interneuron types which show differential vulnerability in the context of an epileptogenic insult. We used the intrahippocampal kainate (KA) mouse model for TLE in which a focal, unilateral KA injection induces status epilepticus (SE) followed by development of granule cell dispersion (GCD) and hippocampal sclerosis surrounding the injection site but not in the intermediate and temporal hippocampus. In this study, we characterized the loss of interneurons with respect to septotemporal position and to differential vulnerability of interneuron populations. To this end, we performed intrahippocampal recordings of the initial SE, in situ hybridization for glutamic acid decarboxylase 67 (GAD67) mRNA and immunohistochemistry for parvalbumin (PV) and neuropeptide Y (NPY) in the early phase of epileptogenesis at 2 days and at 21 days after KA injection, when recurrent epileptic activity and GCD have fully developed. We show that SE extended along the entire septotemporal axis of both hippocampi, but was stronger at distant sites than at the injection site. There was an almost complete loss of interneurons surrounding the injection site and expanding to the intermediate hippocampus already at 2 days but increasing until 21 days. We observed differential vulnerability of PV- and NPY-expressing cells: while the latter were lost at the injection site but preserved at intermediate sites, PV-expressing cells were gone even at sites more temporal than GCD. In addition, we found upregulation of GAD67 mRNA expression in dispersed granule cells and of NPY staining in ipsilateral granule cells and ipsi- and contralateral mossy fibers. Our data thus indicate differential survival capacity of interneurons in the epileptic hippocampus and compensatory mechanisms depending on the hippocampal position.